Strategies for Zinc Uptake in Pseudomonas aeruginosa at the Host–Pathogen Interface - Wang, Shuaitao; Cheng, Juanli; Niu, Yanting; Li, Panxin; Zhang, Xiangqian; Lin, Jinshui (Frontiers in Microbiology, 2021)
As a structural, catalytic, and signaling component, zinc is necessary for the growth and development of plants, animals, and microorganisms. Zinc is also essential for the growth of pathogenic microorganisms and is involved in their metabolism as well as the regulation of various virulence factors. Additionally, zinc is necessary for infection and colonization of pathogenic microorganisms in the host. Upon infection in healthy organisms, the host sequesters zinc both intracellularly and extracellularly to enhance the immune response and prevent the proliferation and infection of the pathogen. Intracellularly, the host manipulates zinc levels through ZIP/ZnT family proteins and various zinc storage proteins. Extracellularly, members of the S100 protein family, such as calgranulin C, sequester zinc to inhibit microbial growth. In the face of these nutritional limitations, bacteria rely on an efficient zinc transport system to maintain zinc supplementation for proliferation and disruption of the host defense system to establish infection. Here, we summarize the strategies for zinc uptake in conditional pathogenic Pseudomonas aeruginosa, including known zinc uptake systems (ZnuABC, HmtA, and ZrmABCD) and the zinc uptake regulator (Zur). In addition, other potential zinc uptake pathways were analyzed. This review systematically summarizes the process of zinc uptake by P. aeruginosa to provide guidance for the development of new drug targets.